Influence of microstructure on the hardness behavior of AISI duplex-2205 composite layer by TIG cladding - Paijan, Lailatul Harina; Maleque, Md. Abdul; Abu Bakar, Mohd Hadzley; Mamat, Mohd Fauzi; Osman, Mohd Hairizal; Rosli, Nor Ana; Asari, Mohd Rashidi (Universiti Putra Malaysia, 2023)
Duplex stainless steel (DSS) material with grade of AISI Duplex-2205 show a decrease performance under aggressive environment which may lead to unanticipated failure due to poor surface properties. Therefore, the surface modification of this material is important to increase the hardness and wear behavior for various applications in the automotive, aerospace and oil and gas industries. The surface modification using SiC ceramic powder with particle size of 60 µm by TIG torch technique has been developed on the surface of AISI Duplex-2205. The TIG torch was employed at different arc energy of 0.480, 0.768 and 1.440 KJ/mm. The composite surface layer was developed via deposition of ceramic particles into AISI Duplex-2205. Based on the experimental results, it was found that the composite layer attained a maximum hardness of 1245 Hv from substrate hardness of 250 Hv for TIG processed at 0.768 KJ/mm. The cross-sectional view of the melt pool for TIG torch melted processed showed a hemispherical shape due to the Gaussian energy distribution of the torch which has been known to have high energy intensity in the center region and gradually decrease to the boarders of the fluid zone. The microstructure demonstrates the formation of the dendrite microstructure due to the complete fusing and re-solidification of SiC in the composite layer that contributes to the hardness enhancement. The formation of dendrites in the melt pool contributes to the hardness and wear enhancement of AISI Duplex2205 which can be used for wear and high temperature applications.